THE ISSUE OF WOMEN AND GIRLS IN THE TURKESTAN PRESS (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes coverage of women's issues in the Turkestan press and how this topic was used to implement the colonial policies of Tsarist Russia and the subsequent Bolshevik government. The primary sources used are articles in the Turkestan News, the Turkestan Regional Newspapers, and other Jadid and Soviet publications, as well as archival materials. It is argued that after the establishment of Soviet power, women's legal equality was proclaimed by the Constitution and decrees. However, in practice, this policy served to separate women from their families and convert them into the workforce in the interests of "socialist construction."